FINITE COPIES OF BARBELL GRAPH AND ITS HARMONIOUS CHROMATIC NUMBER - Ms.V.Kavitha, Dr.R.Govindarajan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper, we find the achromatic number of four copies of complete graphwith their harmonious chromatic number.The harmonious Chromatic number of a graph is the least number of colours in such a colouring.